Living with dementia: increased level of caregiver stress in times of COVID-19 - Cohen, Gabriela (2020)
COVID-19 pandemic has deeply affected the care that older adults with Alzheimer´s Disease(AD) and related disorders received in Argentina. Even though circulation for familycaregivers of subjects with dementia was one of the few exceptions allowed by thegovernment (Ministerio de la Nación, 2020), we observed that most family members decidedto stop visiting their relatives from fear of spreading the disease.COVID-19 epidemic is causing a radical change in the model of dementia care. Before thispandemic, engaging in social activities, performing cognitive and physical activities, andhaving a productive daily routine has been the mainstay therapy. (Austrom, M. G. et al.,2018). To relief caregiver stress, literature has shown that multicomponent strategies suchas avoiding isolation, attending family and group support meetings, sharing the burden ofcare with other family members were useful (Hughes, T.B. et al., 2014). Now, in times ofCOVID-19, we recommend the most strict social isolation, especially for older patients withdementia and other comorbidities who have the highest risk for severe COVID-19 diseaseand mortality. ( Emami et al., 2020).Previous quarantines in human history had a negative psychological impact on outcomessuch as anger, depression, and loneliness in the general population. (Brooks et al., 2020)but the effects on the wellbeing and standard care of subjects with dementia living in thecommunity is not well studied. The objective of our research was to study to what extendmandatory social isolation affected the stress and burden of care of family members caringfor subjects with dementia after the initial four weeks of quarantine and to study therelationship between the severity of the dementia, measured with the Clinical DementiaRating (CDR) (Hughes, C. et al. 1982) and the impact of the negative effects of quarantinein our setting.